Photoredox catalytic cascade radical addition/aromatization of methylene-2-oxazolines: Mild access to C(sp3)-difluoro-oxazole derivatives. Issue 46 (14th November 2019) - Song, Gui-Ting; Qu, Chuan-Hua; Meng, Jiang-Ping; Xu, Zhi-Gang; Zhou, Cheng-He; Chen, Zhong-Zhu
Graphical abstract: Highlights: Cascade pathway. Mild condition. C(sp 3 )-CF2 construction. Excellent reaction selectivity. Abstract: Difluoroalkylated oxazoles were prepared from methylene-2-oxazolines (MOs) and difluoroalkylating reagents via a photoredox strategy. This reaction includes tandem radical addition and subsequent aromatization steps, resulting in 19 difluorinated oxazole derivatives with diverse functionalities and excellent reaction selectivity in the presence of multiple reactivity pathways.